The association of Schistosoma and geohelminth infections with β-cell function and insulin resistance among HIV-infected and HIV-uninfected adults: A cross-sectional study in Tanzania. - George PrayGod; Suzanne Filteau; Nyagosya Range; Kaushik Ramaiya; Kidola Jeremiah; Andrea M Rehman; Rikke Krogh-Madsen; Henrik Friis; Daniel Faurholt-Jepsen (PLoS ONE)
Objectives Data on the role of helminths on diabetes in Africa are limited. We investigated whether Schistosoma and geohelminth infections are associated with β-cell function and insulin resistance among adults. Methods A cross-sectional study was conducted among adults during 2016-2017. Demography, Schistosoma and geohelminth infections, HIV and insulin data were collected. Insulin during an oral glucose tolerance test (fasting, 30, and 120-min), overall insulin secretion index, insulinogenic index, HOMA-β, and HOMA-IR were main outcome measures for β-cell function and insulin resistance, respectively. Generalized estimating equations and generalized linear models assessed the association of Schistosoma and geohelminth infections with outcome measures separately by HIV status. Outcomes were presented as marginal means with 95% CI. Results Data were obtained for 1718 participants. Schistosoma infection was associated with higher 30-min insulin (24.2 mU/L, 95% CI: 6.9, 41.6) and overall insulin secretion index (13.3 pmol/L/mmol/L; 3.7, 22.9) among HIV-uninfected participants but with lower fasting insulin (-0.9 mU/L; -1.6, -0.2), 120-min insulin (-12.0 mU/L; -18.9, -5.1), and HOMA-IR (-0.3 mmol/L; -0.6, -0.05) among HIV-infected participants not yet on antiretroviral therapy (ART). Among HIV-infected participants not on ART, geohelminth infection was associated with lower fasting insulin (-0.9 mU/L; -1.6, -0.2), 120-min insulin (-9.1 mU/L; -17.3, -1.0), HOMA-β (-8.9 mU/L)/(mmol/L; -15.3, -2.6) and overall insulin release index (-5.1 pmol/L/mmol/L; -10.3, 0.02), although this was marginally significant. There was no association among those on ART. Conclusions Schistosoma infection was associated with higher β-cell function among HIV-uninfected participants whereas Schistosoma and geohelminth infections were associated with reduced β-cell function among HIV-infected participants not on ART.